2018
DOI: 10.2174/1381612823666170926150259
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Effects of Early Exposure to Stress, Pain, Opioids and Anaesthetics on Pain Sensitivity and Neurocognition

Abstract: Background Experimental studies have shown that neonatal exposure to stress, pain, opioids and anaesthetics may cause histologic and morphologic changes in the central nervous system with associated functional and behavioural changes in the long term. An important question is whether this holds true for humans also - and in particular for sick neonates who often are exposed to pain and receive anaesthetics and sedatives. Methods In this narrative review, we evaluate the effects of neonatal exposure to stress, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 0 publications
0
19
1
Order By: Relevance
“…Although animal studies have fairly consistently demonstrated brain development to be negatively affected by various classes of drugs, such as anesthetics, benzodiazepines, and to some extent opioids, associations in survivors of neonatal critical illness seem less obvious . This may be due to differences between animal and human studies, resulting in more contradicting conclusions in humans (for a review on this matter, please refer to van den Bosch et al …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although animal studies have fairly consistently demonstrated brain development to be negatively affected by various classes of drugs, such as anesthetics, benzodiazepines, and to some extent opioids, associations in survivors of neonatal critical illness seem less obvious . This may be due to differences between animal and human studies, resulting in more contradicting conclusions in humans (for a review on this matter, please refer to van den Bosch et al …”
Section: Discussionmentioning
confidence: 99%
“…This mechanism may be underlying the negative effects of midazolam found on the hippocampus in preterm infants and may subsequently lead to memory deficits later in life in these children. (Please also refer to a recent review on other proposed mechanisms underlying the effects of analgosedatives and anesthetics on the brain by van den Bosch et al …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations